The effect of dental X-ray on the cells of the human body: Pengaruh radiasi kedokteran gigi terhadap sel tubuh manusia - Sarianoferni; Eha Renwi Astuti (Makassar Dental Journal PDGI Makassar, 2022)
Diagnostic radiology supports the detection of diseases and disorders in the oral cavity, disease progression, and treatment plan-ning, which is indispensable in the field of dentistry. Improvements in imaging technology have consequently increased the use of radiography. The effective dose is relatively low, but the need for repeated radiographic examinations results in an increase in the total dose received. This repeated increases the reception of radiation doses for both patients and workers. This paper reviews the ability of X-rays to penetrate solid objects for diagnostic purposes and the biological effects they cause on human cells. Dental X-ray radiation has many benefits but also has the potential to interfere with the health of cells and tissues. Its use must be ma-naged properly and carefully. Radiation protection procedures for patients, radiographers, and the surrounding environment should be a major concern.